The morphology of fabella and its prevalence in Turkish society - Akkoc, R. F.; Aksu, F.; Emre, E.; Sap, O.; Karatas, A.; Aydin, S.; Ogeturk, M. (Verduci Publisher, 2022)
OBJECTIVE: Fabella is a sesamold whose prevalence is unstable and can be found as bone or cartilage. which changes over time. This study aims to reveal the prevalence. distribution, gender differences, and morphometric characteristics of cartilage and bony fabella in the Turkish population. PATIENTS AND METHODS: The study included 2.035 individuals over 18 years of age. MR images of 121 individuals, whose MR images of both knees could be obtained by anteroposterior and lateral radiographs of the participants, were evaluated retrospectively. RESULTS: The prevalence of fabella was 39.6% in females, 38.4% in males, and 38.8% in total. The prevalence of cartilage fabella was 9.1%, whereas bone fabella incidence was 29.7% regardless of gender. The fabella's mean thickness, width, length, and distance to the epicondylus lateralis femoris were 3.84 mm, 6.04 mm, 6.23, and 31.26 mm, respectively. CONCLUSIONS: The data of this study showing the occurrence and morphometric characteristics of bony and cartilaginous fabella allow early and accurate diagnosis of various pathological conditions caused by fabella.
Keywords: Fabella; Knee; Magnetic resonance images; Prevalence